Haré Que Dios Exista1: Claudio Bertoni y la Teología Negativa - Cussen-Abud, F (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2012)
After an examination of Claudio Bertoni s critical reception, I pick up numerous mentions and refl ections in his interviews that make explicit an infl uence from negative theology. From there, I analize the presence of that religious perspective in his poetry, and I outline some interpretations that would allow to understand his written (and also plastic) work as an attempt to show his complex relationship with God through poverty and despair.
Keywords: Chilean poetry; Claudio bertoni; Negative theology; Religious poetry